Re-bleeding rates and survival after early transjugular intrahepatic portosystemic shunt (TIPS) in clinical practice. Issue 12 (December 2017) - Bucsics, Theresa; Schoder, Maria; Goeschl, Nicolas; Schwabl, Philipp; Mandorfer, Mattias; Diermayr, Magdalena; Feldner, Maria; Riedl, Florian; Bauer, David; Angermayr, Bernhard; Cejna, Manfred; Ferlitsch, Arnulf; et al.
Abstract: Background: Early implantation (<72 h) of a transjugular intrahepatic portosystemic shunt (TIPS) after acute variceal bleeding (AVB) improves survival in highly selected patients. Methods: We retrospectively assessed bleeding control and survival of unselected cirrhotic patients undergoing early TIPS implantation within 72 h. We compared the outcomes to patients meeting early TIPS criteria but receiving late TIPS within 3–28 days after AVB and endoscopic/medical treatment. Results: Forty-nine patients were included. Mean MELD was 14.4 (±4.4). Thirteen patients (26.5%) presented characteristics that were exclusion criteria in previous early TIPS trials (age > 75, CPS > 13, HCC > Milan, previous beta-blocker/band-ligation, renal insufficiency). Bare metal and PTFE-covered stents were used in n = 32 (65.3%) and n = 17 (34.7%) patients, respectively, and showed similar early re-bleeding rates (9.9% vs. 7.1%; p = 0.6905) and bleeding-related mortality (25.0% vs. 23.5%; p = 0.9906). However, overall re-bleeding rate was lower with PTFE-TIPS (7.7% vs. 64.2%; p = 0.0044) over a median follow-up of 18.5 months with a tendency towards improved survival (median 70.5 vs. 13.8 months; p = 0.204). Additional 68 patients meeting stringent criteria but receiving late TIPS also showed a favorable bleeding-related mortality (8.8%), which was not achieved in similar n = 34 patients by a medical/endoscopic strategy with bleeding-related mortality of 35.7%. Conclusions: An early TIPS strategy using covered stents and implementation of 'stringent criteria' results in a favorable outcome in patients with acute variceal bleeding.